School history and History teaching in Brazilian basic schooling: Reflecting on historical courses, contexts and discussions (Research, Society and Development, 2021)
School History and the Teaching of History follow a trajectory of encounters, and disagreements, advances and inflections, reflecting the dynamic and complex Brazilian school reality, from the colonial period to the end of the 1990s. From a methodological approach of bibliographic and documentary research, we describe and reflect on this trajectory, confronting aspects of school policy and legislation in different historical periods. We conclude that, by reflecting on these aspects and itineraries of the Teaching of History and School History, it becomes possible to contribute to the understanding of the processes of teaching and learning and the formation of the historical awareness of people and social groups in the context of schooling Brazilian, and, humbly, also contribute to the increase of debate and research on this theme.